2018
DOI: 10.1299/jfst.2018jfst0018
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on performance characteristics of dielectric discharge plasma actuator using pulsed-dc waveform

Abstract: Dielectric Barrier Discharge Plasma Actuator (DBDPA) is one of active flow control devices, which generates a wall-surface jet utilizing atmospheric discharge. However, the enhancement of the jet is indispensable for application to high Reynolds number flow because the flow speed is typically only up to several meters per second. In recently, it was reported that a Pulsed-DC voltage waveform can drastically improve the jet thrust (McGowan et al., 2016). In the Pulsed-DC waveform, the high DC voltage rapidly dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Similar pulse waveforms were obtained in a previous study [20]. The fall and rise times can be adjusted by using resistors as reported in a previous study [21]. The pulse energy per unit length is calculated as the integral of the instantaneous power [22].…”
mentioning
confidence: 77%
“…Similar pulse waveforms were obtained in a previous study [20]. The fall and rise times can be adjusted by using resistors as reported in a previous study [21]. The pulse energy per unit length is calculated as the integral of the instantaneous power [22].…”
mentioning
confidence: 77%
“…Previous studies have reported on the effectiveness of this approach in flow-separation control [7][8][9][10] and turbulent drag reduction [12][13][14]. Some researchers have also revealed that the characteristics of the induced flow generated by the DBD-PA vary depending on the applied AC voltage waveform [20][21][22]. It has been reported that when the applied voltage has a sinusoidal waveform, a unidirectional flow is induced from the exposed electrode to downstream locations, irrespective of whether the voltage signal is in its positive or negative half cycle.…”
Section: Introductionmentioning
confidence: 99%